Power of Indian traditional foods and their benefits - Sireesha , G (Journal of Postharvest Technology, 2024)
This review research paper aims to comprehensively examine the nutritional and health benefits of traditional Indian foods, shedding light on their potential to promote well-being and address contemporary health challenges. Drawing upon the principles of nutrition, ethnobotany, and traditional knowledge systems, this paper establishes a theoretical framework that underscores the significance of Indian traditional foods in maintaining health and preventing diseases. It explores the synergy between traditional food wisdom and modern nutrition science. A systematic literature review methodology was employed to collect and analyze data from a wide range of sources, including scientific journals, ethnobotanical texts, and nutritional databases. The selected studies covered various aspects of Indian traditional foods, including ingredients, preparation methods, and their impact on health. The findings of this research reveal that Indian traditional foods encompass a diverse array of ingredients, preparation techniques, and regional variations that collectively provide a balanced and nutritionally rich diet. These foods are often rich in essential nutrients, antioxidants, and bioactive compounds, which are associated with numerous health benefits, including improved digestion, enhanced immunity, and reduced risk of chronic diseases such as diabetes and heart disease. This review highlights the potential of Indian traditional foods as a valuable resource for promoting public health and nutrition. Understanding and incorporating these foods into modern diets can have practical implications for addressing contemporary health challenges. Additionally, this research underscores the importance of preserving and promoting traditional food knowledge, which is essential for maintaining cultural diversity and sustainable food systems. This research contributes to the existing © The Author(s) This is an Open Access article licensed under a Creative Commons license: Attribution 4.0 International body of knowledge by providing a comprehensive synthesis of the nutritional and health benefits of traditional Indian foods. It bridges the gap between traditional wisdom and modern science, emphasizing the importance of preserving and integrating traditional dietary practices in a rapidly changing world.